The impacts of domestic violence and feminicide as an extreme consequence (International Seven Journal of Multidisciplinary, 2023)
The article in question aims to highlight the daily reflexes of domestic violence against women, as well as its impact on society. It is noted that the problem stems from a gender inequality contained in the social body in a deep-rooted way, due to the adversity of a patriarchal society. Although it is a problem that comes from centuries ago, there are still Brazilian women who suffer with this reality, as was seen in the year 2022, in which 31 thousand complaints of women who still experience violence were made. Moreover, even after the creation of the Maria da Penha Law, a revolutionary milestone for Brazilian women, there is still the question whether it is really put into practice, since many cases are neglected and may even evolve into feminicide. Moreover, it is known that threats made by the aggressors and their impunity in several known cases of violence discourage the victims from denouncing them. This fact has angered many social groups composed of women who want the law to be implemented in a fair and safe way. DOI: 10.56238/isevmjv1n2-003